A parallelogram has an area of 288 square centimeters and a height of 12 centimeters.What is the length of the base of the parallelogram?



_________A parallelogram has an area of 288 square centimeters and a height of 12 centimeters.



What is the length of the base of the parallelogram?



____cm

Answers

Answer 1
Answer: 288/12=24 Therefore, the length of the base is 24 cm.

Related Questions

A student skipped a step when she tried to convert 15 hours to seconds,and she got the following incorrect result ?15 hours(60 seconds),/1 minute=900seconds
A video game is on sale for 30% off the regular price of $50.
What is 19% of 72? I NEED TO KNOW HOW YOU GOT THE ANSWER TO!!
Vicki measured the midnight temperatures in 4 locations in Alaska. The temperatures were -7, -2, 1, 4. What is the mean absolute deviation of the temperatures?The mean is -1
2x^3+17x^2+23x-42; 2x+7

at Mary's party 4/8 of the guest had chocolate ice cream and 3/8 of the guest had strawberry ice cream . what fraction of the ice cream was either chocolate or strawberry

Answers

7/8 because you add 4/8 and 3/8 together which is equal to 7/8.
7/8 I believe, as 4/8 had chocolate ice cream and 3/8 had strawberry and we don't know what the remaining 1/8 had, so just add who had strawberry and who had chocolate together and that will give you the probability.

If g(t) = 2/(t + 3), then g() = 2/(4a + 3).

Answers

The value will be 4a.

Expression

In mathematics, an expression is defined as a set of numbers and mathematical operations that is formed according to rules which is dependent on the context.  

Given to us,

equation 1,

g(t) = (2)/((t + 3))

equation 2,

g(\ \ ) = (2)/((4a + 3))

Let's assume t=4a,

substituting the value of t in equation1, we get

g(t) = (2)/((t + 3))

g(4a) = (2)/((4a + 3))

As we can see we get equation 2 again, therefore, the value will be 4a.

Learn more about the expression:

brainly.com/question/13947055

Answer:

g(4a) = (2)/(4a + 3)

Step-by-step explanation:

Given the function is g(t) = (2)/(t + 3) ........... (1)

Now, we are given that g() = (2)/(4a + 3) .......... (2)

Now, the left hand side of both the above equations (1) and (2) are similar and the only change is that t is replaced by 4a.

Therefore, the equation (2) can be written as  

g(4a) = (2)/(4a + 3) (Answer)

Since we know that if g(t) = (2)/(t + 3) then g(k) = (2)/(k + 3), where k is any real value.

Can someone plz help me with this

Answers

it would be the first one :)

Use transformations to solve the equation. y/6 = -2 A. y = –12

B. y = –3

C. y = 3

D. y = 12

Answers

y/6 = -2

y = -2x6

y = -12

Find the measure of b

Answers

Answer:

75

Step-by-step explanation:

I have answered ur question

the answer to your question is 75

A water cooler holds 4.8 gallons of water. The container is .65 full. How many gallons of water are in the cooler?

Answers

I think that it is 4.15 I'm not sure pls no hate